2018
DOI: 10.1245/s10434-018-6825-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional Market Competition and the Use of Immediate Breast Reconstruction After Mastectomy

Abstract: Synopsis Background Prior work has shown that the competitiveness of the market in which hospitals operate is associated with use of surgical procedures. We examined the association between regional market competition and use of breast reconstruction in women with breast cancer and ductal carcinoma in-situ undergoing mastectomy. Methods Women who underwent mastectomy from 2010–2011 recorded in the National Inpatient Sample were selected. The competitive market environment for each hospital in which patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Existing studies using HHI as a measure of market concentration in breast reconstruction have shown that HHI is associated with an increased odds of immediate breast reconstruction and of breast reconstruction with a free flap. 58,59 In terms of the association with commercial rates, Cerullo et al 60 found that for privately insured patients who undergo breast reconstruction, increasing market concentration (ie, increasing HHI) was associated with decreasing costs and procedural markup (ie, pro- portional difference between charges and average procedural costs). 60 This study was limited, however, by using Healthcare Cost and Utilization Project data based on cost-to-charge ratios, which have questionable accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies using HHI as a measure of market concentration in breast reconstruction have shown that HHI is associated with an increased odds of immediate breast reconstruction and of breast reconstruction with a free flap. 58,59 In terms of the association with commercial rates, Cerullo et al 60 found that for privately insured patients who undergo breast reconstruction, increasing market concentration (ie, increasing HHI) was associated with decreasing costs and procedural markup (ie, pro- portional difference between charges and average procedural costs). 60 This study was limited, however, by using Healthcare Cost and Utilization Project data based on cost-to-charge ratios, which have questionable accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Higher prices in more concentrated markets may ultimately be passed down to patients in the form of higher premiums and deductibles. Existing studies using HHI as a measure of market concentration in breast reconstruction have shown that HHI is associated with an increased odds of immediate breast reconstruction and of breast reconstruction with a free flap . In terms of the association with commercial rates, Cerullo et al found that for privately insured patients who undergo breast reconstruction, increasing market concentration (ie, increasing HHI) was associated with decreasing costs and procedural markup (ie, proportional difference between charges and average procedural costs) .…”
Section: Discussionmentioning
confidence: 99%
“…Operating in a competitive market often leads to hospitals investing in more high-technology services and equipment, particularly surgical fields. 19 22 Wright et al 19 found the effect of market competition on access to postmastectomy breast reconstruction to be independent of other clinical and demographic factors. Although only one-third of women in noncompetitive environments received postmastectomy breast reconstruction, over 50% of women were in receipt in competitive environments.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Furthermore, there is a growing body of the literature suggesting that market forces significantly impact the adoption and delivery of advance surgical care. 19 22 …”
Section: Introductionmentioning
confidence: 99%
“… 3 Another study demonstrated that women with breast cancer were more likely to receive immediate reconstruction after mastectomy if they were treated in the most competitive hospitals. 4 However, there remains a lack of empirical evidence across different tumor types and treatment modalities.…”
Section: Introductionmentioning
confidence: 99%